Pair-Bonding as Inclusion of Other in the Self: A Literature Review - Branand, Brittany; Mashek, Debra; Aron, Arthur (Frontiers in Psychology, 2019)
This article surveys scholarship on the self-expansion model principle of inclusion of other in the self (IOS) as it relates to long-term pair-bonding (i.e., enduring adult romantic monogamous relationships). First, we introduce the concept of IOS and then provide a brief overview of prior research. We then review compelling extensions and findings related to a variety of relational concepts such as perspective taking (Bernstein, Laurent, Nelson, & Laurent, 2015), social comparison (Thai & Lockwood, 2015), self-determination (Weinstein, Rodriguez, Knee, & Kumashiro, 2016), humor (Treger, Sprecher, & Erber, 2013), and pain contagion (Martire, Keefe, Schulz, Stephens, & Mogle, 2013). Next, we explore two recent theoretical directions of the principle—the two-dimensional model of relational self-change (McIntyre, Mattingly, & Lewandowski, 2015) and the perceived inclusion of the other in the self (IOS-perceived) construct (Tomlinson & Aron, 2013). Considering these findings and their relation to pair-bonding, we propose important future directions of the IOS principle of the self-expansion model.